Hot cross bun sign: A case report of multiple system atrophy presenting predominantly as respiratory insufficiency - Margiben Tusharbhai Bhatt; R Sunil (Indian Journal of Respiratory Care, 2021)
Multiple system atrophy (MSA) was a multisystem disorder usually associated with Parkinsonism, MSA-p subtype or with cerebellar ataxia, and MSA-c subtype. Respiratory insufficiency can be a part of the clinical manifestation of multiple-system atrophy. It can sometimes present as primary respiratory failure, mild motor function disturbance, or autonomic dysfunction. In this article, we present a case of a 60-year-old lady who was admitted to the intensive care unit with fever and shortness of breath of 3 days duration with an initial working diagnosis of community-acquired pneumonia requiring invasive mechanical ventilation. She had a history of daytime sleepiness and gait disturbance. A thorough neurological evaluation was done to ascertain the cause of difficulty in weaning her off the ventilator. Magnetic resonance imaging of the brain revealed atrophy of bilateral superior cerebellar peduncles and pons with the “hot cross bun sign” suggestive of multiple system atrophy. Thus, a prompt neurological examination and work-up, including brain imaging, are mandated in dealing with such cases of difficult to wean patients.